Digital Art : Artistic Changes in Technology Era - Andri Sahata Sitanggang; Evriliano Pratama (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Technological developments over the past few decades have brought about major changes in the world of art. One of the most striking advances is the advent of artificial intelligence (AI), which is now not only a tool but also capable of creating works of art independently. This situation raises an important question in the world of contemporary art: how can human artists remain relevant and maintain the originality of their work amid the emergence of machine-generated artworks? This study aims to explore how technology, particularly AI, influences the creation, distribution, and reception of artworks. The primary focus of the research is on public perceptions of technology's role in art today. Through the distribution of questionnaires to the community around the researcher, the results obtained will show that the presence of technology has changed the way the relationship between artists, works, and audiences is formed. Digital technology opens up new possibilities in artistic creation, but simultaneously raises ethical and existential challenges for artists. Nevertheless, questions arise about how curation, authenticity, and aesthetic value are maintained in art. Therefore, this research emphasizes the importance of adaptation, cross-disciplinary collaboration, and support from inclusive policies and ecosystems to enable artists to continue to thrive in the dynamically evolving art landscape.